2014
DOI: 10.1109/jphotov.2014.2335738
|View full text |Cite
|
Sign up to set email alerts
|

Class AAA LED-Based Solar Simulator for Steady-State Measurements and Light Soaking

Abstract: Recent improvements in light-emitting diode (LED) technology has allowed for the use of LEDs for solar simulators with excellent characteristics. In this paper, we present a solar simulator prototype fully based on LEDs. Our prototype has been designed specifically for light soaking and current-voltage (I(V )) measurements of amorphous silicon solar cells. With 11 different LED types, the spectrum from 400 to 750 nm can be adapted to any reference spectrum-such as AM1.5g-with a spectral match corresponding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 5 publications
3
23
1
Order By: Relevance
“…The author used low ripple power supply with the constant current control as the LED driver. This is in accordance with the study results of Bazzi [3] and the design of Novickovas [1] and Stuckelberger [12] whose results showed that the uniformity measurements were also in class A. …”
Section: ) Short-term Instability Testsupporting
confidence: 92%
See 2 more Smart Citations
“…The author used low ripple power supply with the constant current control as the LED driver. This is in accordance with the study results of Bazzi [3] and the design of Novickovas [1] and Stuckelberger [12] whose results showed that the uniformity measurements were also in class A. …”
Section: ) Short-term Instability Testsupporting
confidence: 92%
“…Stuckelberger. [12] presented the class AAA LEDs-based solar simulator. The simulator is comprised of 11 colors of 19 LEDs (399-728 n.m.).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…III B and III D. The other four solar cells were contacted by ultrasonic soldering and light soaked with in-situ measurement of the LID kinetics. These measurements were performed with three-sun-equivalent illumination for one day at 50 C. A dedicated solar simulator 43 fully based on light-emitting diodes (LEDs) and built in-house was used for these measurements, which are presented in Sec. III C.…”
Section: Methodsmentioning
confidence: 99%
“…The cost of the entire system is below $ 20,000, with most of the budget going towards the data acquisition hardware. [6][7][8]. LED based solar simulators are also commercially available, somewhere within the $25K range for a class AAA simulator of 2x2 inch illumination, which is more or less the same price range compared to a xenon lamp based counterpart of the same dimensions [5].…”
mentioning
confidence: 99%